ANALYSIS OF THE EFFECT OF CAPITAL ADEQUACY RATIO, NON PERFORMING FINANCING, AND FINANCING TO DEPOSIT RATIO ON PROFITABILITY: A CASE STUDY ON ISLAMIC COMMERCIAL BANKS IN INDONESIA - Ema Muawanah; Imronudin Imronudin (Journal of Management and Islamic Finance, 2021)
This study aims to analyze the effect of Capital Adequacy Ratio (CAR), Non-Performing Financing (NPF), and Financing to Deposit Ratio (FDR) on Profitability (Case Study on Islamic Commercial Banks in Indonesia). This research used secondary data in the form of Islamic Commercial Bank financial statements. The population in this study is Islamic Commercial Banks listed on the Indonesia Stock Exchange in 2016-2018. The sampling technique employed was purposive sampling. A sample of 3 banks was obtained. Multiple linear regression was used. Classical assumption analysis was done prior to data analysis. Hypothesis testing used t-test, F test, and the coefficient of determination (R2). The results of this study indicated that CAR has a positive and significant effect on profitability, NPF has a negative and significant effect on profitability and FDR has a negative and no significant effect on profitability. Meanwhile, the independent variables together have an effect on profitability. The result of the coefficient of determination test shows that 61.1% of the profitability of Islamic Commercial Banks in Indonesia is explained by the variables of CAR, NPF, and FDR, while the remaining 38.4% is explained by other variables outside the model.